Cell-free supernatant of probiotic bacteria exerted antibiofilm and antibacterial activities against Pseudomonas aeruginosa: A novel biotic therapy - Drumond, Mariana Martins; Tapia-Costa, Ana Paula; Neumann, Elisabeth; Nunes, Álvaro Cantini; Barbosa, Jorge Wanderson; Kassuha, Diego E.; Mancha-Agresti, Pamela (Frontiers in Pharmacology, 2023)
Aims: Verify the antibacterial and antibiofilm action of cell-free spent medium (CFSM) from four Lactic Acid Bacteria with potential probiotic characteristics (Lactiplantibacillus plantarum, Lactobacillus acidophilus, Lactobacillus johnsonii and Lactobacillus delbrueckii) against two Pseudomonas aeruginosa strains. Main Methods: MIC and MBC of the CFSM, the antibacterial activity through analysis of inhibition zones formation and inhibition of planktonic cultures were carried out. It was also verified the influence of the increase in the concentration of CFSM on the growth of pathogenic strains and the determination of the anti-adhesive activity of CFSM in the biofilm formation (crystal violet and MTT assays) was developed which were corroborated with Scanning Electron Microscopy. Key Findings: The relation between MIC and MBC values showed either bactericidal or bacteriostatic effect for all the CFSM tested, for Pseudomonas aeruginosa 9027TM and 27853TM strains. The CFSM supplemental of 18 or 22%; 20 or 22%; 46 or 48%, and 50 or 54 % of L. acidophilus, L. delbrueckii, L. plantarum and L. johnsonii, respectively, were able to completely inhibit growing of both pathogens’ strains. Antibiofilm activity of these CFSM in three biofilms conditions (precoated, co-incubated and preformed) demonstrated values ranging between 40 to 80% of biofilm inhibition and similar results were observed for cell viability. Significance: This work shows strong evidence that the postbiotic derived from different lactobacilli could be practical as an adjuvant therapy for reducing the use of antibiotics being good candidates to overcome the growing challenge of hospitaller infections due to this pathogen.